Frequency and Distribution of ABO and Rhesus Blood Groups among Pregnant Women Attending the Obstetrics and Gynecology Department at Tobruk Medical Center - Salem Zaed; Asfiedeen Saleh; Salima Omran; Saleh Saad (AlQalam Journal of Medical and Applied Sciences, 2025)
Blood transfusion procedures make the ABO and rhesus (Rh) blood group systems extremely important. The present study was to determine the prevalence of different blood groups and Rh factors in a random population sample among pregnant women attending the obstetrics and gynecology department at Tobruk Medical Center. Blood group and Rh factor determination was carried out by the antigen-antibody agglutination test tube from January 2022 to December 2022, and encompassed 3144 subjects. Data on the frequency of ABO and Rh(D) blood groups were reported in numbers and percentages. The percentages of various groups of subjects, respectively, were recorded as 38.3% for blood group O, 33.4 % for blood group A, 21.4% for blood group B, and 6.6% for blood group AB. The Rh-positive and negative distribution in the studied population was 86.7% and 13.3%, respectively. It is concluded that the O blood group was more prevalent, whereas AB was the least common. This study will support the development of a database for blood transfusion services. It would also reduce the risk of erythroblastosis foetalis in newborns.